2022
DOI: 10.3390/molecules28010058
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavanone from Chromolaena tacotana (Klatt) R. M. King and H. Rob, Promotes Apoptosis in Human Breast Cancer Cells by Downregulating Antiapoptotic Proteins

Abstract: Chromolaena tacotana is a source of flavonoids with antiproliferative properties in human breast cancer cells, the most common neoplasm diagnosed in patients worldwide. Until now, the mechanisms of cell death related to the antiproliferative activity of its flavonoids have not been elucidated. In this study, a novel flavanone (3′,4′-dihydroxy-5,7-dimethoxy-flavanone) was isolated from the plant leaves and identified by nuclear magnetic resonance (NMR) and mass spectrometry (MS). This molecule selectively inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Some flavanones and their derivatives possess anticancer activities. Tacotanina, a 3 ′ ,4 ′ -dihydroxy-5,7-dimethoxyflavonone isolated from the leaves of Chromolaena tacotana, inhibits the cell proliferation of triple-negative human breast cancer cell lines MDA-MB-231 and MCF-7 [54]. The scientists noted a significant inactivation of the anti-apoptotic protein Bcl-2 and the activation of effector caspase-3 and/or 7 within the breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some flavanones and their derivatives possess anticancer activities. Tacotanina, a 3 ′ ,4 ′ -dihydroxy-5,7-dimethoxyflavonone isolated from the leaves of Chromolaena tacotana, inhibits the cell proliferation of triple-negative human breast cancer cell lines MDA-MB-231 and MCF-7 [54]. The scientists noted a significant inactivation of the anti-apoptotic protein Bcl-2 and the activation of effector caspase-3 and/or 7 within the breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that natural chalcones, including butein, xanthohumol, isoliquiritigenin, chalcotanina, and flavokawains, may exhibit cytotoxic effects, particularly inducing apoptosis in breast cancer (BC) cells [ 17 , 28 , 43 , 45 ]. However, prior to this study, there was no evidence demonstrating the simultaneous induction of both apoptosis and autophagy in BC cells by flavokawains (FKCs).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of apoptosis by chalcones, particularly through the activation of caspase-3, is a well-documented phenomenon [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In our study, the data suggested that DDC preferentially activated caspase-3 over caspase-7 in MDA-MB-231 cells, as illustrated in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations